Conocimiento y percepción de la marca país Colombia por parte de las Mipymes del sector turismo - Forero, Sara (2024)
The country brand has become a fundamental strategy in government agendas, since it contributes to the generation of national identity and contributes to the promotion of international visibility strategies. Particularly, the Colombian country brand has an interest in articulating with the private business sector, however, it has been evident that many companies do not know such a strategy nor do they give it the respective value. Thus, the objective of this research is to understand the current knowledge and perception of the Colombian country brand by MSMEs in the tourism sector, choosing MSMEs for their current contribution to the country's economy and job creation. For this purpose, an exploratory qualitative research was carried out, with 5 participating MSMEs from the department of Cundinamarca. The main findings suggest that the MSMEs in the tourism sector studied have basic knowledge about the country brand, they intend to be allies of it, but they do not believe that this generates deep commercial contributions.